Structure of tyrosine aminotransferase from Leishmania infantum. Issue 5 (1st May 2014) - Moreno, M. A.; Abramov, A.; Abendroth, J.; Alonso, A.; Zhang, S.; Alcolea, P. J.; Edwards, T.; Lorimer, D.; Myler, P. J.; Larraga, V.
<x xml:space="preserve">Abstract</x> The trypanosomatid parasite Leishmania infantum is the causative agent of visceral leishmaniasis (VL), which is usually fatal unless treated. VL has an incidence of 0.5 million cases every year and is an important opportunistic co‐infection in HIV/AIDS. Tyrosine aminotransferase (TAT) has an important role in the metabolism of trypanosomatids, catalyzing the first step in the degradation pathway of aromatic amino acids, which are ultimately converted into their corresponding L‐2‐oxoacids. Unlike the enzyme in Trypanosoma cruzi and mammals, L. infantum TAT (LiTAT) is not able to transaminate ketoglutarate. Here, the structure of LiTAT at 2.35 Å resolution is reported, and it is confirmed that the presence of two Leishmania‐specific residues (Gln55 and Asn58) explains, at least in part, this specific reactivity. The difference in substrate specificity between leishmanial and mammalian TAT and the importance of this enzyme in parasite metabolism suggest that it may be a useful target in the development of new drugs against leishmaniasis.